Urgensi Karakter Orang Tua dalam Membangun Karakter Anak Di Masa Pandemi Covid-19 (Studi Kasus di Desa Sridadi) Kecamatan Muara Bulian Kabupaten Batang Hari: The Urgency of Parents' Character in Building Children's Character During the Covid-19 Pandemic (Case Study in Sridadi Village) Muara Bulian District, Batang Hari Regency - Pahmi Pahmi (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2022)
This study aims to find out the extent of the Urgency of Parental Character in The Formation of Children's Character During the Covid-19 Pandemic (Case Study in Sridadi Village) that the Urgency of Parental Character in The Formation of Children's Character During Covid-19 Pandemic is still not optimal. This is also strengthened by the phenomena of the rapid progress of the global and digital world. Of course, it can have a positive and negative impact on children's morals. If it has a positive impact, it is naturally not a problem. However, if it has a negative impact, then it is necessary to conduct research. It is this moral deviation that is of concern to the researcher. For example, there is still a weak understanding of the importance of child character building because they still think that character building is only in formal education (school) and children are not paid enough attention or are not educated optimally, so children have poor character. A poor character such as speaking less politely, lack of concern for fellow friends, dishonesty towards parents, and lack of respect for their elders. This research uses a qualitative approach with data collection techniques using observation methods, interviews, and documentation. Then, researchers conduct analysis with domain analysis, taxonomic analysis, and component analysis. The last step that the researcher takes is to triangulate the data to find its validity of the data. Conclusions that can be drawn from the description in the previous discussion are the Urgency of Parental Character in The Formation of Children's Character During the Covid-19 Pandemic (Case Study in Sridadi Village), namely: the existence of a child character who lies, stays up late at night even until dawn, does not say greetings when he wants to enter the house, skips school, speeding riding a motorcycle on the street, the child's character that is difficult to form, obstacles due to technological advances, and social factors, bringing the child closer to religious activities, setting an example, advising and inviting the child persuasively, giving attention to the child.